Significance and Conservation of Birds of the Genus of Bee-eater (MEROPS) in Uzbekistan - Yangiboyev Elmurod Chorshanbiyevich; Shodiyeva Fotima Ochilovna; Kholboev Fakhriddin Rohmonkulovich; Rakhimov Matnazar Shomurodovich (مجلة بغداد للعلوم)
The purpose of this article is to identify and evaluate the importance of birds of the genus Merops (European Bee-eater -Merops apiaster and Blue-cheeked Bee-eater -Merops persicus) in Uzbekistan, as well as to develop recommendations aimed at solving some problems associated with its conservation. As a result of the study, in the aspect of biocenotic relations, the natural significance of these species was revealed. The economic value is determined and analyzed in beekeeping farms. From the study of the remains of food contained in the stomachs, throats and nests of M.apiaster, a preliminary list of the main species of the food spectrum has been compiled. Based on the bioacoustic repellent "Korshun-8", a new, more effective bioacoustic repellent has been developed to repel bee-eaters. To solve some of the problems associated with the conservation of bee-eaters, recommendations have been developed aimed at preventing the illegal extermination of bee-eaters, preserving their nesting colonies, etc.